Reduced retort processing time improves canning quality of fast‐cooking dry beans (Phaseolus vulgaris L.). (19th May 2020) - Bassett, Amber; Dolan, Kirk D; Cichy, Karen
Abstract: BACKGROUND: While it is generally accepted that fast‐cooking germplasm benefits consumers, benefits to the canning industry have not been established. Genotypes with good canning quality withstand the canning process while remaining intact with good appearance, but canning protocols used by breeders typically involve long processing times that may overcook some genotypes. The goal of this study was to identify whether cooking time influences canning quality in dry beans and whether reducing processing time could improve canning quality of fast‐cooking genotypes. RESULTS: A set of 20 yellow bean genotypes including Ervilha, PI527538 and 18 derived recombinant inbred lines were selected for their varied cooking times. By comparing the genotypes processed across five retort times, differences in canning quality were identified. All genotypes performed better when processed for less time than the standard 45 min, but canning quality was highest at 10 min for fast‐ and medium‐cooking genotypes and 15 min for slow‐cooking genotypes. Cooking time was correlated positively with texture and intactness and negatively with washed‐drained weights, indicating that slower cooking beans have higher canning quality. Color changed with retort processing such that longer times produced darker beans with more red and yellow. CONCLUSIONS: While fast‐cooking beans exhibited lower canning quality at standard processing times, reduced retort processing time allowed them to meet quality standards while still maintaining food safety. By accounting for cooking time as a component of canning quality, breeders can develop varieties that are convenient and cost efficient for preparation for both consumers and the canning industry. Published 2020. This article is a U.S. Government work and is in the public domain in the USA.